Tracing field lines that are reconnecting, or expanding, or both - Qiu, Jiong (Frontiers in Astronomy and Space Sciences, 2024)
The explosive release of energy in the solar atmosphere is driven magnetically, but the mechanisms that trigger the onset of the eruption remain controversial. In the case of flares and coronal mass ejections (CMEs), ideal or non-ideal instabilities usually occur in the corona, but it is difficult to obtain direct observations and diagnostics there. To overcome this difficulty, we analyze observational signatures in the upper chromosphere or transition region, particularly brightening and dimming at the base of coronal magnetic structures. In this paper, we examine the time evolution of spatially resolved light curves in two eruptive flares and identify a variety of tempo-spatial sequences of brightening and dimming, such as dimming followed by brightening and dimming preceded by brightening. These brightening–dimming sequences are indicative of the configuration of energy release in the form of plasma heating or bulk motion. We demonstrate the potential of using these analyses to diagnose the properties of magnetic reconnection and plasma expansion in the corona during the early stages of the eruption.